 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
Solve the following pair of linear equations by the substitution method (3x/2) – (5y/3) = -2 (x/3) + (y/2) = (13/6)

```
one month ago Anand Kumar Pandey
1583 Points
```							Dear StudentGiven(3x/2)-(5y/3) = -2and(x/3) + (y/2) = 13/6 are the two equations.From 1st equation,we get(3/2)x = -2 + (5y/3)⇒ x = 2(-6+5y)/9 = (-12+10y)/9 ………………………(1)Putting the value of x in the given second equation to get((-12+10y)/9)/3 + y/2 = 13/6⇒y/2 = 13/6 –( (-12+10y)/27 ) + y/2 = 13/6Now, substitute the value of y in equation (1)we get(3x/2) – 5(3)/3 = -2⇒ (3x/2) – 5 = -2⇒ x = 2Therefore,x = 2 and y = 3.Thanks.
```
one month ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions